2020
DOI: 10.1016/j.nicl.2020.102395
|View full text |Cite
|
Sign up to set email alerts
|

Orbitofrontal cortex grey matter volume is related to children’s depressive symptoms

Abstract: Highlights Healthy children’s orbitofrontal grey matter volume related to depressive symptoms. Maternal depression history is unrelated to children’s brain structure. Sex moderates relationship between orbitofrontal structure and depressive symptoms. Girls have negative orbitofrontal grey mater volume-depressive symptom relationship. Boys have positive orbitofrontal grey matter volume-depressive symptom relationship.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 127 publications
1
4
0
Order By: Relevance
“…Although our findings are generally consistent with the previous literature showing significantly reduced frontal, parietal, temporal, orbito-frontal cortex volumes [8,22], our results of amygdala, striatum, and hippocampus volumes in MDD patients are partly inconsistent with the previous literature [10,34–36]. Here, we found, unexpectedly, that striatal and amygdala volumes were significantly increased in the MDD group when compared to the control group while hippocampal volumes were unchanged.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Although our findings are generally consistent with the previous literature showing significantly reduced frontal, parietal, temporal, orbito-frontal cortex volumes [8,22], our results of amygdala, striatum, and hippocampus volumes in MDD patients are partly inconsistent with the previous literature [10,34–36]. Here, we found, unexpectedly, that striatal and amygdala volumes were significantly increased in the MDD group when compared to the control group while hippocampal volumes were unchanged.…”
Section: Discussionsupporting
confidence: 78%
“…Herewith, there are several studies demonstrating significant alterations in brain volumes in MDD patients. Overall, these studies have indicated that hippocampus, insula, prefrontal, and orbitofrontal cortex are among the most affected regions during the course of depression [6–9].…”
Section: Introductionmentioning
confidence: 99%
“…For an 11-year-long follow-up study, this retention rate is better than expected (Teague et al, 2018 ). Chi-square and t-tests were used to compare the current subsample to members of original sample who did not participate in this follow-up study; the groups did not significantly different when compared on caregiver or youth age, socioeconomic status, ethnicity, maternal lifetime history of anxious or depressive disorders (assessed via clinical interview; see Vandermeer et al, 2020 , for more details), or youths’ depressive or anxious symptoms at age 11 (i.e., the most proximal previous assessment wave available; all ps > 0.05). Data were collected using Qualtrics XM (Qualtrics, USA), with separate individual survey links sent by email to parents and youths to allow for independent self-report.…”
Section: Methodsmentioning
confidence: 99%
“…Data for this study were collected from children and their mothers across four separate assessment visits (for more details see Vandermeer et al, 2020). Briefly, this included: 1) a phone interview to complete the parent-report portion of the Kiddie Schedule for Affective Disorders and Schizophrenia, Present and Lifetime Version (K-SADS-PL; Kaufman et al, 1997); 2) a home visit to complete the child self-report portion of the K-SADS-PL, gather MFC audio stimuli, and complete questionnaire measures; 3) a lab visit to complete the SCID-I/NP with moms and the Trier Social Stress Task for Children (Buske-Kirschbaum et al, 1997) with child participants (not discussed in this paper); 4) a MRI visit.…”
Section: Procedures and Measuresmentioning
confidence: 99%